If things go South: The renewed policy of sport mega events allocation and its implications for future research. (December 2021) - Graeff, Billy; Knijnik, Jorge
The past few decades have seen an increase of sport mega events (SMEs) held outside the Global North. This tendency has been accompanied by a growing public expenditure in these events. This paper employs selected Global South SMEs to discuss this trend. By critically analysing public documents, biddings and reports, the study traces comparisons between 21st-century Global South and Global North SMEs expenditures, in the revenue of franchise owners (FIFA and the International Olympic Committee), in construction costs within the budgets and in the costs related to security. This comprehensive and intertwined investigation shows the need for new analytical tools – such as the Renewed Policy of Sport Mega Events Allocation, a concept developed here - to better capture the central questions posed by the challenges of 'SMEs going South'.